Performance of Soft Clay Foundation Improved Using RCA Columns - Alaa H. J. Al-Rkaby, Ahmed Hussein (Mathematical Statistician and Engineering Applications, 2023)
Improving the bearing capacity of fine clay is one of the main tasks of stone columns in this field study, three different types of stone columns made of recycled concrete aggregate were used: single, grid (2*2), and a group of eight stone columns The grid pattern (2 * 2) of the stone column is reinforced with geogrid. The results show that the use of stone columns made of recycled concrete aggregates improves the bearing capacity of soft clay soils. Compared with natural soil, the use of stone columns with a single, grid (2 * 2), and a group of eight stone columns increases the bearing capacity by 5%, 23%, and 72%, respectively. The use of stone column reinforced with geogrid improves the bearing capacity of the soil by 144% compared to the column without reinforcement